GROWTH RESPONSE AND YIELD OF PURPLE EGGPLANT ON VARIOUS PLANTING MEDIA AND LIQUID ORGANIC FERTILIZER - Maryana, Maryana; S. Padmini, Oktavia; Indri, Nia (Journal TECHNO, 2023)
Purple eggplant is a seasonal vegetable that contains a lot of fiber and few calories and is rich in manganese, folate, potassium, vitamins K and C, small amounts of niacin, magnesium and copper. The research aims to determine the composition of various planting media compositions and liquid organic fertilizers that are best for the growth and yield of purple eggplant plants. The research was carried out at the Experimental Garden of the Faculty of Agriculture, National Development University "Veteran" Yogyakarta. This research used a factorial design arranged in a completely randomized design. The first factor is the composition of the planting medium, soil, sand, and manure with volume ratios of (2:1:1), (1:1:2), (1:2:1), and (1:2:2). The second factor is the type of liquid organic fertilizer consisting of rabbit urine, cow urine, rice washing water and liquid smoke. The research results showed that the composition of the planting media and the application of liquid organic fertilizer from rabbit urine, cow urine, rice washing water and liquid smoke had no significant effect on all parameters, except for the diameter of purple eggplant stems per plant.